2020
DOI: 10.18502/jad.v13i4.2240
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Aedes (Stegomyia) albopictus (Diptera: Culicidae) in Algiers, the Capital City of Algeria

Abstract: Background: Based on the reporting of the presence of stripped mosquitoes by a citizen in the Algiers residential neighborhood of Bir-Khadem, where residents experienced huge daytime mosquito nuisance an entomological inves-tigation was carried out in July 2016. Methods: Ovitraps and BG sentinel traps baited with Lure were used during three consecutive days to collect adult mosquitoes. Eighteen residential houses of the Bir-Khadem neighborhood were also inspected to search larvae breed-ing sites s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
2
15
0
3
Order By: Relevance
“…albopictus in urban settings would be expected since the number of infested houses has increased in 2019 during the warm season (Bouattour A., com. pers) and as it is the case today in Algeria [ 38 ]. Thereby it seems critical to evaluate the susceptibility of a local Ae .…”
Section: Introductionmentioning
confidence: 99%
“…albopictus in urban settings would be expected since the number of infested houses has increased in 2019 during the warm season (Bouattour A., com. pers) and as it is the case today in Algeria [ 38 ]. Thereby it seems critical to evaluate the susceptibility of a local Ae .…”
Section: Introductionmentioning
confidence: 99%
“…Such data can be obtained by filling out a questionnaire indicating the level of nuisance expressed on a Likert scale. A study conducted in Algeria demonstrated that perception of citizens can help to identify occurrence of Aedes albopictus in a residential neighbourhood in Bir-Khadem [ 52 ]. This helped to put in place vector control measures that could prevent the propagation of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…This helped to put in place vector control measures that could prevent the propagation of Ae. albopictus to other areas and to avoid the massive use of insecticides for vector control, which could ultimately lead to insecticide resistance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actuellement, l'invasion du moustique tigre Aedes (Stegomyia) albopictus (Skuse, 1894) au Nord d'Afrique est une préoccupation majeure. Sa première détection en Algérie a été en 2010 au niveau de la région de Tizi-Ouzou (Izri et al, 2011), il a été ensuite détecté à Oran en 2015 (Benallal et al, 2016) et au capitale Alger en 2016 (Benallal et al,2019). C'est un moustique originaire des forêts humides du Sud-est Asiatique (Darriet, 2019).…”
Section: Introductionunclassified
“…La présence de cette espèce peut engendrer un risque réel, lié à l'apparition des épidémies de Chikungunia et de Dengue (Delaunay et al, 2009). Dans ce contexte, plusieurs travaux ont été réalisés sur les Culicidae en Algérie, notamment ceux de Rehimi & Soltani (1999), Messai et al (2010), Izri et al (2011), Berchi et al (2012), Bouabida et al (2012), Lafri et al (2014), Benallal et al (2015Benallal et al ( ,2016Benallal et al ( , 2019, Benbetka et al (2018), Benhissen et al (2018), Hamaidia & Berchi (2018), Nabti & Bounechada (2019), Kharoubi et al (2020). La présente étude a été consacrée à la détermination des espèces Culicidiennes inventoriées au niveau de la région de Tizi-Ouzou (Nord d'Algérie), et l'exploitation des résultats par les indices écologiques afin de préciser l'abondance relative et les fréquences d'occurrence.…”
Section: Introductionunclassified